Szkoła dla dziecka – cyfrowego tubylca. Postrzeganie szkoły przez uczniów edukacji wczesnoszkolnej – uczestników projektu „Wychować człowieka mądrego” - Adrianna Sarnat-Ciastko (Problemy Wczesnej Edukacji)
The main goal of this article is to show how early education pupils see school as a place of their development. This presentation is built upon two resources used by the contemporary Polish school – information and communication technologies and personalization of education. The presented image is based on data collected through on-line questionnaires from 1,772 pupils from Classes I–III at primary schools taking part in the project of implementing the method of tutoring “Raise a wise man”. As a result of the analysis, it can be stated that the group of the youngest students rates the school best, and the growing need to contact tutors who build with them individual relationships based on trust may indicate room for modeling the proper use of information and communication technologies.